Comparative Analysis of Financial Performance before and After Mergers and Acquisitions in Companies Listed on the Indonesia Stock Exchange - Lindiyani Lindiyani; Nizwan Zukhri; Ari Agung Nugroho (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2023)
This study aims to determine the significance of differences in company financial performance before and after mergers or acquisitions. The variables used to measure a company's financial performance consist of the illiquidity ratio (CR), activity ratio (TATO), solvency ratio (DER,) and profitability ratio (NPM, ROA). The population of this study is all sectors of companies listed on the Indonesia Stock Exchange (IDX) which carried out mergers and acquisitions for the 2016-2020 period totaling 38 companies. iSample was determined by the purposive sampling method and obtained by 17 companies. The financial statements used and analyzed are two years before and two years after the merger or acquisition. The data analysis methods in this study include the Kolmogorov-Smirnov One-Sample normality test, the PairedI sample T-Test, and Wilcoxon'si Signed Ranksi Test. The results of hypothesis testing found that there were no significant differences in all financial ratios before and after mergers and acquisitions. Keywords: Acquisition, Financial Performance, Merger